2017
DOI: 10.1103/physrevb.96.155132
|View full text |Cite
|
Sign up to set email alerts
|

Crystal-field splittings in rare-earth-based hard magnets: Anab initioapproach

Abstract: We apply the first-principles density functional theory + dynamical mean field theory framework to evaluate the crystal-field splitting on rare-earth sites in hard magnetic intermetallics. An atomic (Hubbard-I) approximation is employed for local correlations on the rare-earth 4f shell and selfconsistency in the charge density is implemented. We reduce the density functional theory selfinteraction contribution to the crystal-field splitting by properly averaging the 4f charge density before recalculating the o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
59
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 64 publications
6
59
2
Order By: Relevance
“…Interestingly, a recent neutron diffraction experiment reported even larger local moments in SmCo 5 , which add up to give a resultant magnetization in excess of 12µ B /FU [73]. Studies employing DMFT and open-core calculations have reported smaller Sm total moments of approximately -0.3µ B , which would bring the total SmCo 5 moment closer to 8µ B /FU [49][50][51]. Earlier GGA+U calculations found a much larger total moment of 9.9µ B /FU due to a ferromagnetic alignment of Sm and Co spins.…”
Section: Comparison To Experimentsmentioning
confidence: 99%
“…Interestingly, a recent neutron diffraction experiment reported even larger local moments in SmCo 5 , which add up to give a resultant magnetization in excess of 12µ B /FU [73]. Studies employing DMFT and open-core calculations have reported smaller Sm total moments of approximately -0.3µ B , which would bring the total SmCo 5 moment closer to 8µ B /FU [49][50][51]. Earlier GGA+U calculations found a much larger total moment of 9.9µ B /FU due to a ferromagnetic alignment of Sm and Co spins.…”
Section: Comparison To Experimentsmentioning
confidence: 99%
“…First, RE-TM magnetism originates from both itinerant electrons and more localized lanthanide 4f electrons [11]. Although the local spindensity approximation to density-functional theory [12] (DFT) satisfactorily describes the itinerant electrons, the 4f electrons require specialist techniques like dynamical mean field theory [13,14], the local self-interaction correction (LSIC) [15], the open-core approximation [16][17][18], or Hubbard +U models [19,20]. Second, DFT calculations are most easily performed at zero temperature, but under actual operating conditions the RE-TM magnetic moments are subject to a considerable level of thermal disorder [21].…”
mentioning
confidence: 99%
“…An impressive body of theoretical work based on crystal field theory has been built up over decades [10], where model parameters are determined from experiment (e.g. Ref.[11]) or electronic structure calculations [12][13][14]. An alternative and increasingly more common approach is to use these electronic structure calculations, usually based on density-functional theory (DFT), to calculate the material's magnetic properties directly without recourse to the crystal field picture [15][16][17][18][19].Calculating the MCA of RE-TM magnets presents a number of challenges to electronic structure theory.…”
mentioning
confidence: 99%